Easy Microsoft® Windows® XP Home Edition, Second Edition - O'Hara, Shelley (Que, 2011)
Easy Windows XP, Home Edition 2nd Edition covers more than 150 of the most important tasks, ranging from the simple features such as opening a folder to more advanced topics such as installing new hardware or restoring a system. This book uses visual learning to appeal to the most common users of Windows XP - the home user.